Sectoral analysis of Spanish investment in Latin America - Toral, Pablo (2000)
The presence of Spanish companies in Latin America became a phenomenon of important economic and social consequences in the 1990s. Three fourths of the capital invested by Spanish firms occurred in banking, energy and telecommunications. These three industries make up the economic infrastructure of a market and, therefore, investments in those sectors have important implications for the future economic development of the host countries. A detailed sectoral analysis shows that the arrival of the Spanish investors was not a spontaneous phenomenon. Rather, it was a defensive move by the Spanish firms, supported by the Spanish government, to gain access to new markets in advance of the internal liberalization in the European Union, which would make the Spanish firms come into direct competition with large and supposedly more competitive European firms. The structural reforms implemented by the Latin American governments in the 1990s and the opening of their markets to foreign investors worked as powerful incentives for the Spanish firms. Latin America offered them new markets to improve their competitiveness and to generate additional resources to compensate for the potential loss of business in Spain to European competitors. The conditions in Latin America were appropriate for the introduction of their products, which were mostly related to the development of infrastructure in all three sectors. MERCOSUR, Chile, and Peru were the main recipients of Spanish investment.